Bevacizumab in recurrent WHO grades II–III glioma - Annakib, Soufyan; Rigau, Valérie; Darlix, Amélie; Gozé, Catherine; Duffau, Hugues; Bauchet, Luc; Jarlier, Marta; Fabbro, Michel (Frontiers in Oncology, 2023)
Purpose The management of recurrent WHO grades II–III (rGII–III) glioma is not well established. This study describes the clinical outcomes in patients who received bevacizumab as rescue treatment. Methods In this retrospective study, the main inclusion criteria were as follows: adult patients with histologicaly proved rGII–III glioma according 2016 WHO classification treated with bevacizumab from 2011 to 2019, T1 contrast enhancement on MRI. Efficacy was assessed using the high-grade glioma 2017 Response Assessment in Neuro-Oncology criteria. Progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan–Meier method. Results Eighty-one patients were included (M/F ratio: 1.7, median age at diagnosis: 38 years) among whom 46 (56.8%) had an initial diagnosis of grade II glioma. Previous treatments included at least one surgical intervention, radiotherapy (98.8%), and ≥ 2 chemotherapy lines (64.2%). After bevacizumab initiation, partial response, stable disease, and progressive disease were observed in 27.2%, 22.2%, and 50.6% of patients. The median PFS and OS were 4.9 months (95% confidence interval [CI] 3.7–6.1) and 7.6 months (95% CI 5.5–9.9). Bevacizumab severe toxicity occurred in 12.3%. Twenty-four (29.6%) patients discontinued bevacizumab without radiological progression. Oligodendroglioma and age ≥ 38 years at diagnosis were more frequent in this subgroup (odds ratio = 0.24, 95% CI 0.07–0.84, p = 0.023 and 0.36, 95% CI 0.13–0.99, p = 0.042). Ten of these 24 patients were alive at 12 months and two patients at 8 years after bevacizumab initiation, without any subsequent treatment. Conclusion Bevacizumab can be an option for heavily pretreated patients with rGII–III glioma with contrast enhancement. In our study, bevacizumab displayed prolonged activity in a subgroup of patients.